1974
DOI: 10.1136/jcp.27.5.392
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the serum alkaline phosphatases in liver diseases

Abstract: The two main alkaline phosphatase isoenzymes in serum from patients with extrahepatic biliary obstruction have been purified. Properties of these isoenzymes, such as electrophoretic mobility, separation on gel filtration, ultracentrifugation characteristics, Michaelis constants, and sensitivity to neuraminidase have been studied and compared with the isoenzymes of liver and bile. The results show that there is an abnormal isoenzyme in the serum from these patients and that this isoenzyme is similar but not ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

1978
1978
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 20 publications
1
33
0
1
Order By: Relevance
“…However, the profound elevations in the serum AST and ALP in the CFA-treated rats could also have arisen from extra-hepatic sources such as acute myocardial infarction and/or bone diseases and remodeling (Kantharia and Woolf, 1987;Aida, 1993). Thus, the profound elevation in the serum ALP in the arthritic rats strongly points to the establishment of an active bone lesion such as arthritis in the CFA-treated rats which is in complete agreement with results of other studies (Price and Sammons, 1974;Rosalki et al, 1982;. Further elevations in the serum levels of AST and ALP caused by oral treatment with 100-400 mg/kg of HEAC in both pre-and post-arthritic rat models could possibly have arisen from worsening of the chemically induced arthritis or remodeling phase of bone healing.…”
Section: Discussionsupporting
confidence: 81%
“…However, the profound elevations in the serum AST and ALP in the CFA-treated rats could also have arisen from extra-hepatic sources such as acute myocardial infarction and/or bone diseases and remodeling (Kantharia and Woolf, 1987;Aida, 1993). Thus, the profound elevation in the serum ALP in the arthritic rats strongly points to the establishment of an active bone lesion such as arthritis in the CFA-treated rats which is in complete agreement with results of other studies (Price and Sammons, 1974;Rosalki et al, 1982;. Further elevations in the serum levels of AST and ALP caused by oral treatment with 100-400 mg/kg of HEAC in both pre-and post-arthritic rat models could possibly have arisen from worsening of the chemically induced arthritis or remodeling phase of bone healing.…”
Section: Discussionsupporting
confidence: 81%
“…Although all enzyme biomarkers of cholestasis are membrane bound, the majority of serum cholephilic enzyme activity is believed to be normally hydrophilic (Price and Sammons, 1974;De Broe et al, 1975;Tsuji et al, 1980). While this could imply the production of specialized secretory forms of these enzymes, it has actually been shown that the enzymes are synthesized in their normal form but then become solubilized through the loss of their hydrophobic membrane anchoring motifs Hoffmann, 1995, 1999).…”
Section: Cellular Redistribution Of Cholephilic Enzyme Activitymentioning
confidence: 99%
“…Gombos (1976) also described protein denaturation by organic solvents in extraction of membranes. However, studies using other enzymes have shown that they may be delipidated by organic solvents and that activity may either be retained (Price and Sammons, 1974), or reactivation may take place by readdition of phospholipid (Vore et al, 1974;IngelmanSundberg, 1977). It is not yet known whether the loss of y-GT activity which occurs with butanol is caused by denaturation or by delipidation, but Discussion to butanol: 88 % had more than 75 % residual activity, and most patients retained 100% of y-GT activity.…”
Section: Group 4 Reflected Normal Sera In Their Responsementioning
confidence: 99%